Cellular and humoral immune responses and breakthrough infections after three SARS-CoV-2 mRNA vaccine doses - Almendro-Vázquez, Patricia; Chivite-Lacaba, Marta; Utrero-Rico, Alberto; González-Cuadrado, Cecilia; Laguna-Goya, Rocio; Moreno-Batanero, Miguel; Sánchez-Paz, Laura; Luczkowiak, Joanna; Labiod, Nuria; Folgueira, María Dolores; Delgado, Rafael; Paz-Artal, Estela (Frontiers in Immunology, 2022)
Background: SARS-CoV-2 vaccination has proven the most effective measure to control the COVID-19 pandemic. Booster doses are being administered with limited knowledge on their need and effect on immunity. Objective: To determine the duration of specific T cells, antibodies and neutralization after 2-dose vaccination, to assess the effect of a third dose on adaptive immunity and to explore correlates of protection against breakthrough infection. Methods: 12-month longitudinal assessment of SARS-CoV-2-specific T cells, IgG and neutralizing antibodies triggered by 2 BNT162b2 doses followed by a third mRNA-1273 dose in a cohort of 77 healthcare workers: 17 with SARS-CoV-2 infection prior to vaccination (recovered) and 60 naïve. Results: Peak levels of cellular and humoral response were achieved 2 weeks after the second dose. Antibodies declined thereafter while T cells reached a plateau 3 months after vaccination. The decline in neutralization was specially marked in naïve individuals and it was this group who benefited most from the third dose, which resulted in a 20.9-fold increase in neutralization. Overall, recovered individuals maintained higher levels of T cells, antibodies and neutralization 1 to 6 months post-vaccination than naïve. Seventeen asymptomatic or mild SARS-CoV-2 breakthrough infections were reported during follow-up, only in naïve individuals. This viral exposure boosted adaptive immunity. High peak levels of T cells and neutralizing antibodies 15 days post-vaccination associated with protection from breakthrough infections. Conclusion: Booster vaccination in naïve individuals and the inclusion of viral antigens other than spike in future vaccine formulations could be useful strategies to prevent SARS-CoV-2 breakthrough infections.